Detection and localization of surgically resectable cancers with a multi-analyte blood test - Cohen, Joshua D; Li, Lu; Wang, Yuxuan; Thoburn, Christopher; Afsari, Bahman; Danilova, Ludmila; Douville, Christopher; Javed, Ammar A; Wong, Fay; Mattox, Austin; Hruban, Ralph H; Wolfgang, Christopher L; et al. (Science (American Association for the Advancement of Science), 2018)
Earlier detection is key to reducing cancer deaths. Here, we describe a blood test that can detect eight common cancer types through assessment of the levels of circulating proteins and mutations in cell-free DNA. We applied this test, called CancerSEEK, to 1005 patients with nonmetastatic, clinically detected cancers of the ovary, liver, stomach, pancreas, esophagus, colorectum, lung, or breast. CancerSEEK tests were positive in a median of 70% of the eight cancer types. The sensitivities ranged from 69 to 98% for the detection of five cancer types (ovary, liver, stomach, pancreas, and esophagus) for which there are no screening tests available for average-risk individuals. The specificity of CancerSEEK was greater than 99%: only 7 of 812 healthy controls scored positive. In addition, CancerSEEK localized the cancer to a small number of anatomic sites in a median of 83% of the patients.